(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation of using traditional medicine by people in Nam Dinh province from 2019 to 2021. Method: The study was conducted according to a cross-sectional descriptive method based on interviewing people at households with structured questionnaires to survey the actual use of traditional medicine of people from January 2019 to the end of October 2021. The standard used in the study is representative of the household that organizes information about the health status and health performance of household members. Numbers after entering data collection into Excel, cleaning, exporting to SPSS 23.0 software. Algorithm to use: frequency, percentage, when squared, applying the 50% confidence threshold, the results are statistically significant when p < 0.05. Results: The percentage of households using traditional medicine in the past 3 years (2019- 2021) was 86.9%, mainly using the combined method of traditional medicine and modern medicine with 51.7%, the rate of using traditional medicine alone accounted for 48.3%. The main purpose of people using traditional medicine is to treat diseases with 51.9%, a low rate is used to treat diseases after treatment with traditional medicine does not cure with 3.4%. The main reason people choose traditional medicine is a chronic disease with 71.1%. The form of traditional medicine is the most used by the people with 44.2% of the people choosing, the non-drug methods account for the lowest proportion with 24.0% of the people choosing. Households growing medicinal plants account for 58.6%. Conclusions: Using traditional medicine has certain advantages in treating diseases. It is necessary to promote communication so that people clearly understand the effects, benefits, and advantages of traditional medicine in health care.